Cumulant/bispectrum model structure identification applied to a pH neutralization process - Emara-Shabaik, H.E. (1996)
A process model structure identification criteria based on the cumulants and bispectrum of output response data is applied to a laboratory-scale pH neutralization process. The resulting model structure is appropriate and is consistent with a priori physical information.